Anxiety and Depression in Patients Waiting for a Kidney Transplantation - Abdullah, Sangar; Akıncı, Ozan; Altuntaş Abdullah, Elif (Cerrahpaşa Medical Journal, 2021)
Objective: The objective of this cross-sectional study is to evaluate the depression and anxiety levels of patients who are on a cadaveric kidney transplantation waiting list due to end-stage renal disease. Methods: A total of 200 patients were involved in the study. Group 1 included 100 patients aged 18-75 years diagnosed with end-stage renal disease and on the transplant waiting list. Group 2 (control group) included 100 healthy volunteers aged 18-75 years with no chronic disease. Data were obtained by using demographic information form, Beck’s Depression Inventory, State-Trait Anxiety Inventory. Beck’s Depression Inventory and State-Trait Anxiety Inve scores were statistically compared between groups. In addition, in group 1 patients, depression and anxiety scores were compared in terms of gender and the presence of other chronic diseases. Results: The Beck’s Depression Inventory, STAI scores of group 1 were observed to be statistically significantly higher than group 2 (P < .05). When the anxiety levels of the group 1 patients were evaluated according to gender, Beck’s Depression Inventory and State-Trait Anxiety Inve mean scores were significantly higher in women than in men (P < .05). In addition, Beck’s Depression Inventory and State- Trait Anxiety Inve scores of group 1 patients with chronic renal failure as well as other chronic diseases were found to be statistically significantly higher than those without additional chronic diseases (P < .05). The Beck’s Depression Inventory and State-Trait Anxiety Inve scores of the patients in group 1 without any other chronic disease were significantly higher than the patients in group 2 (P < .05). Conclusion: Patients with end-stage renal failure and on the transplant waiting list have more tendency toward depression and anxiety. Cite this article as: Abdullah S, Altuntaş Abdullah E, Akıncı O. Anxiety and depression in patients waiting for a kidney transplantation. Cerrahpaşa Med J. 2021;45(3):192-196.